2005
DOI: 10.1038/nm1206
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin regulates brain amyloid β peptide Aβ42 through modulation of proteolytic degradation

Abstract: Expression of somatostatin in the brain declines during aging in various mammals including apes and humans. A prominent decrease in this neuropeptide also represents a pathological characteristic of Alzheimer disease. Using in vitro and in vivo paradigms, we show that somatostatin regulates the metabolism of amyloid beta peptide (Abeta), the primary pathogenic agent of Alzheimer disease, in the brain through modulating proteolytic degradation catalyzed by neprilysin. Among various effector candidates, only som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
262
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(279 citation statements)
references
References 26 publications
14
262
1
2
Order By: Relevance
“…Somatostatin-14 (SST- 14) 4 is a small cyclic peptide hormone secreted by hypothalamus, one of the well known functions of which is to inhibit the release of growth hormone (16). Other important functions of somatostatin-14 include inhibition of gastrin and gastric acid secretion, inhibition of insulin and glucagon secretion in pancreas, and regulation of amyloid-␤ peptide, A␤42, in brain (17)(18)(19) Somatostatin-14 has previously been reported to form amyloid fibrils in vitro (4,20). In this study, we first show that somatostatin-14 is stored as amyloid-like aggregates in rat hypothalamus tissues (Fig.…”
mentioning
confidence: 99%
“…Somatostatin-14 (SST- 14) 4 is a small cyclic peptide hormone secreted by hypothalamus, one of the well known functions of which is to inhibit the release of growth hormone (16). Other important functions of somatostatin-14 include inhibition of gastrin and gastric acid secretion, inhibition of insulin and glucagon secretion in pancreas, and regulation of amyloid-␤ peptide, A␤42, in brain (17)(18)(19) Somatostatin-14 has previously been reported to form amyloid fibrils in vitro (4,20). In this study, we first show that somatostatin-14 is stored as amyloid-like aggregates in rat hypothalamus tissues (Fig.…”
mentioning
confidence: 99%
“…This effect is clearly mediated via SRIF receptors since both an SSTR antagonist (BIM23056) and a Gi inhibitor (pertussis toxin) inhibit neprilysin activation. Thirdly, in the hippocampus of SRIF-precursor protein-knockout mice, neprilysin activity was found to be significantly lower than that in wild-type mice (Saito et al, 2005). In addition, a 50% increase in A1-42 levels was (Figure 1), thus leading to late-onset sporadic AD.…”
Section: Page 11 Of 31mentioning
confidence: 91%
“…First, both neprilysin expression and SRIF content in the brain decrease during aging. Secondly, in primary cortical neurons, Saito et al (2005) have demonstrated that SRIF significantly increases neuronal neprilysin activity and decreases A1-42 levels in the culture medium. This effect is clearly mediated via SRIF receptors since both an SSTR antagonist (BIM23056) and a Gi inhibitor (pertussis toxin) inhibit neprilysin activation.…”
Section: Page 11 Of 31mentioning
confidence: 97%
“…During aging, NEP and IDE levels are selectively reduced in vulnerable regions of the brain, such as the hippocampus, where the Aβ appears to be readily deposited first, but not in the cerebellum and striatum, where no significant Aβ accumulation occurs [38,39]. The aging-induced reduction of NEP levels has been attributed, at least partially, to age-dependent depletion of somatostatin, which stimulates NEP expression [40]. In AD brains, NEP levels were significantly lower in regions with high levels of plaque, such as the hippocampus and temporal gyrus [41], further supporting the notion that the deficiency in NEP or IDE might contribute to region-specific Aβ accumulation in sporadic AD.…”
Section: Regulation Of Aβ-degrading Enzymesmentioning
confidence: 99%
“…For example, somatostatin significantly elevated neuronal NEP activity, probably by affecting protein turnover and cellular localization [40]. Agonists for somatostatin receptors might be used to augment the Aβ-degrading activities of NEPs [40].…”
Section: Regulation Of Aβ-degrading Enzymesmentioning
confidence: 99%